Highly dispersible magnetic nanoparticles modified by double quaternary ammonium surfactants for efficient harvesting of oleaginous microalgae. (20th November 2021) - Qin, Wenqi; Zhang, Siqi; Yang, Shujuan; Lin, Feilin; Zhou, Qichang; Gong, Houkui; Zhao, Xinyu; He, Furui; Zhou, Yang; Feng, Yuhong; Yu, Gaobo; Liu, Yuanyuan; et al.
Abstract: Microalgae have been known as a promising sustainable resource for bioenergy cleaner production. Herein, a series of highly dispersible novel magnetic quaternary ammonium cationic surfactants (Fe3 O4 @DQn, n = 1, 2, 3) for the efficient harvesting of oleaginous Chlorella pyrenoidosa ( C. pyrenoidosa ) have been investigated. The Fe3 O4 @DQn capture microalgae process can be divided into a three-step operation (i.e., flocculation, separation, and recycle). For harvesting C. pyrenoidosa, the Fe3 O4 @DQn has both a high recovery efficiency (>98.4%) and a short flocculation time (2 min). In addition, the reused Fe3 O4 @DQ2 can maintain a high recovery efficiency (92.31%) with five cycling times. Moreover, the N -[3-(Trimethoxysilyl)propyl]ethylenediamine (TMPED) amount and the pH value both have a positive influence on the C. pyrenoidosa harvesting. It is worth noting that the dual effect of quaternary ammonium cationic surfactant, strong positively charged and hydrophobic properties, leads to a higher harvesting efficiency of microalgae. Furthermore, the results of particle size distribution and turbiscan stability index (TSI) show that a higher specific surface area, a smaller polydispersity index and TSI value of the Fe3 O4 @DQn can make a more excellent adsorption and dispersion properties. Finally, the Fe3 O4 @DQn might provide a promising high cost-performance to harvesting of oleaginous microalgae due to the better economic viability. Highlights: A novel magnetic quaternary ammonium cationic surfactant (Fe3 O4 @DQn) was prepared. Strong positive and hydrophobic dual effect can enhance Fe3 O4 @DQn's properties. C. pyrenoidosa can be flocculated by Fe3 O4 @DQn with a high recovery efficiency. The reused Fe3 O4 @DQn after five times can still harvest C. pyrenoidosa efficiently. Fe3 O4 @DQn has a high cost-performance to harvesting of oleaginous microalgae.